Mulheres Jornalistas: histórias, memórias e vidas - Oliveira, Edileusa Martins de (2017)
This document is an academic research and report on the construction of the documentary "Women Journalists: Stories, Memories and Lives", which aims to immerse in the memories and perceptions of six women journalists who have worked and worked in media vehicles in Natal, Large northern river. Through the accounts of life, we seek to achieve, through their memories and experiences, perceptions of professional practices, the direction of journalism and discernment about career and gender relations in newsrooms. For the narrative construction and approach of the documentary, we use some elements indicated by PUCCINI (2007 and 2009) and BERNARD (2008), with a concern to let them speak freely about the topics researched. With this, it was possible to capture memories and affections of strong and determined women who have distinct visions of life and profession. They will tell us what is behind women's journalism. As a methodological option, we used the studies of PAULILO (1999), CHIZZOTTI (2011) and MARCONI and LAKATOS (2013) in the application of the History of Life method. The bibliographical research on the history of journalism in Rio Grande do Norte was based on CARVALHO (2014), ROCHA NETO (2005) and GOMES (2004). The reflection on documentary filmmaking was based on the theories of NICHOLS (2008) and PENAFRIA (1999). With the perceptions and life histories of each interviewee, it was possible to verify the moral, ethical and political discourses, as well as the marks of the gender relations, that was spelled out in their works. We also note that, although there is an increase in the number of women in journalism faculties and newsrooms, they are still stigmatized in the labor market with the lack of opportunity for access to leadership and management positions in journalistic vehicles and corporations.